Optimization of process parameters for mechanical properties of Al- Al2O3- graphite hybrid composite fabricated using stir casting process. (2022) - Divakar, S.; Chitharthan, S.; Shanmugapriyan, V.G; Thalaieswaran, S.; Gopinath, K.
Abstract: Due to their high strength-to-weight ratio and other mechanical qualities, composite materials are widely employed in the automotive, aerospace, and defence industries. While Al 5052 alloy has good corrosion resistance, its hardness restricts its applicability. At melting temperatures of 700 °C, 750 °C, and 800 °C, and reinforcement pre-heat temperatures of 250 °C, 300 °C, and 350 °C, samples were made using Al 5052 reinforced with Aluminium oxide Al2 O3 (2%, 4%, and 6% by volume) and graphite (0.5 %). The Taguchi L9 orthogonal design of experiments was used to perform the studies. The distribution of reinforcement and the microstructure of composites were investigated using an inverted microscope. Microhardness and wear tests were done, respectively, utilizing microhardness testing equipment and pin-on-disc apparatus. Tensile testing equipment was used to determine the tensile strength of the composite materials. The results indicate that Al2 O3 MMC having 0.5% graphite, and 6% Al2 O3 fabricated at 750 °C with reinforcement preheated at 300 °C shows a hardness, wear resistance and tensile strength of 87 Hv, 220.9 MPa and 81 µm respectively, whilst the presence of graphite increases the material's wear resistance.